2013
DOI: 10.1123/jsm.27.5.349
|View full text |Cite
|
Sign up to set email alerts
|

Examining Sense of Community in Sport: Developing the Multidimensional ‘SCS’ Scale

Abstract: As scholars conduct more research on the social benefits of community sport, the need for an instrument to measure sense of community is increasingly necessary. Utilizing previous grounded theory research specific to sport and community building, the purpose of this study was to test previous sport and sense of community theory through the creation and validation of a measurement scale to gauge sense of community. The authors tested a 21-item tool comprised of 6-subscales (i.e., Administrative Consideration, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 43 publications
2
66
0
Order By: Relevance
“…Their work in the youth sport setting supported six of the seven original Sport and Sense of Community factors 2013a). Specifically, Voluntary Action was the only item that did not hold up within their model of sense of community in sport (Warner et al, 2013). This anomaly was attributed to the youth athletes' obvious dependence on their caregivers for support, and removed this factor 'in an attempt to create a more parsimonious scale that can be applicable across sport settings ' (p. 359).…”
Section: Sport Volunteerism and Sense Of Communitymentioning
confidence: 99%
See 4 more Smart Citations
“…Their work in the youth sport setting supported six of the seven original Sport and Sense of Community factors 2013a). Specifically, Voluntary Action was the only item that did not hold up within their model of sense of community in sport (Warner et al, 2013). This anomaly was attributed to the youth athletes' obvious dependence on their caregivers for support, and removed this factor 'in an attempt to create a more parsimonious scale that can be applicable across sport settings ' (p. 359).…”
Section: Sport Volunteerism and Sense Of Communitymentioning
confidence: 99%
“…athletes. In particular, work by Warner, Dixon, and Chalip (2012), and Warner et al (2013) demonstrated a sense of community benefits both individuals and organizations. After extensive interviews and focus groups with 80 athletes, the summation of 2013a) work generated a Sport and Sense of Community theory.…”
Section: Sport Volunteerism and Sense Of Communitymentioning
confidence: 99%
See 3 more Smart Citations